CORRELATION OF DEVIANCE IN ARTERIAL OXYGENATION WITH SEVERITY OF CHRONIC LIVER DISEASE - Shaukat, Al-Aman; Zar, Adnan; Zuhaid, Muhammad; Afridi, Safa Saadat; Khan, Abid Ullah (Journal of Ayub Medical College Abbottabad, 2016)
Background: Hepatitis B and C related chronic liver diseases have led to development of a serious threat to the people of South Asia. The main aim of this study was to evaluate the correlation of magnitude of arterial deoxygention to the severity of liver disease. Methods: It was a hospital based cross sectional descriptive study, carried out in the Medical Department of Khyber Teaching Hospital Peshawar. All in all 115 patients were assessed for the severity of the liver diseases and were correlated with arterial deoxygenation using linear regression models. Results: Male to female ratio was 1.5:1. Males infected with hepatitis B, hepatitis C and both were 9, 60 and 1, while females suffered from hepatitis B, Hepatitis C and both were 2, 42 and 1 respectively. The linear relationship between A-a DO2 with severity of liver disease showed positive correlation while PO2 showed negative correlation with severity of liver disease. Conclusion: There was a positive correlation between A-a DO2 and severity of liver diseases while PO2 and severity of liver diseases showed negative correlation Keywords: Chronic liver disease, severity, arterial oxygenation, deviance, correlation